Efficacy of the Optilume paclitaxel drug-coated balloon after urethroplasty: short-term results from a multicenter study - Maia VanDyke; Eshan Joshi; Brian Ceballos; Adam Baumgarten; Ethan Matz; Kayla S. Graham; Maxim J. McKibben; Ahmad Imam; Lucas Wiegand; Bryce Franzen; Steven Hudak (Therapeutic Advances in Urology)
Background: The Optilume ® paclitaxel drug-coated balloon (DCB) is a relatively new-to-market alternative in the management of male anterior urethral stricture disease. The pivotal trial excluded patients with a history of urethroplasty, although these strictures may be amenable to endoscopic management. Therefore, we sought to assess the efficacy of the DCB in the management of recurrent strictures following urethroplasty. Methods: A retrospective, multi-institutional review of male patients undergoing DCB dilation from 1/1/2022 to 11/1/2023 by five surgeons at four institutions was performed. Patients were stratified by history of urethroplasty; demographics, stricture characteristics, and outcomes (surgical success, time to recurrence). Success was defined as freedom from re-intervention in patients with at least 3 months of follow-up. Results: Among the 122 cases assessed, 33 (27.0%) had previously undergone urethroplasty. Patients in the urethroplasty group were younger than those in the control group (51.6 vs 58.8 years, p  = 0.022). The two groups were otherwise similar with regard to background characteristics and comorbidities. Patients in both groups had similar stricture characteristics with short bulbar strictures being the most common. When compared to the control group, those with a history of prior urethroplasty had a greater median number of interventions prior to DCB treatment (3 vs 1, p  < 0.001). Postoperative cystoscopy was performed in 37 cases, with similar patency rates between groups ( p  > 0.999). Early success rates were similarly high in both groups (80.0% post-urethroplasty vs 88.9% control, p  = 0.338), although follow-up was limited to a median of 3.5 months in the urethroplasty group and 2.9 months in the control group ( p  = 0.069). Conclusion: Despite a greater number of prior surgical interventions, patients with a history of urethroplasty achieve similarly high success rates after treatment with DCB compared to those without a history of urethroplasty.